2014
DOI: 10.7314/apjcp.2014.15.21.9355
|View full text |Cite
|
Sign up to set email alerts
|

New formulated "DOX-MTX-loaded Nanoparticles" Down-regulate HER2 Gene Expression and Improve the Clinical Outcome in OSCCs Model in Rat: the Effect of IV and Oral Modalities

Abstract: Background: Oral squamous cell carcinoma (OSCC) remains as one of the most difficult malignancies to control because of its high propensity for local invasion and cervical lymph node dissemination. In this study, we evaluate the efficacy of our novel pH and temperature sensitive doxorubicin-methotrexate-loaded nanoparticles (DOX-MTX NP) in affecting HER2 expression profile in OSCC model in rat. Results: DOX-MTX-nanoparticle complexes caused significant decrease in mRNA level of HER2 compared to untreated cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Apoptosis and DNA damage was significantly increased in the dual-drug-loaded liposome group compared to other controls. Abbasi et al [53][54][55] examined stimuli-responsive cationic mesoporous silica NPs loaded with MTX and Dox on a 4-NQO-induced oral cavity SCC rat model. Both free and nanoforms of Dox combined with MTX were orally or IV administrated for 14 weeks.…”
Section: Doxorubicinmentioning
confidence: 99%
“…Apoptosis and DNA damage was significantly increased in the dual-drug-loaded liposome group compared to other controls. Abbasi et al [53][54][55] examined stimuli-responsive cationic mesoporous silica NPs loaded with MTX and Dox on a 4-NQO-induced oral cavity SCC rat model. Both free and nanoforms of Dox combined with MTX were orally or IV administrated for 14 weeks.…”
Section: Doxorubicinmentioning
confidence: 99%
“…These 4 cancers account for almost half of the total cancer deaths among men and women, with more than one-quarter of all cancer deaths due to lung cancer. An urgent need in cancer control today is to develop effective and affordable approaches to the early detection, diagnosis, and treatment of cancer (Abbasi et al, 2014b;Siegel et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The HSC-3 cell line is highly invasive; therefore, the present study aimed to detect the mechanism of MTX-induced apoptosis in HSC3 cells. MTX is active in oral cancer cells, but exhibits marked limitations regarding cell uptake and site specificity as it is associated with certain highly toxic effects (17). This was also evaluated via an apoptosis assay in HSC 3 cells; M-LP-F7 increased the percentage of apoptotic cells 3-fold, compared with MTX alone.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HPMC and PVA exhibited an extended release of almost 40% of the drug in 12 h. Abbasi et al (17) formulated a doxorubicin-methotrexate (MTX)-loaded nanoparticle to attenuate oral cancer growth, and evaluated them in an oral squamous cell carcinoma (OSCC) rat model. Additionally, this study group identified that the downregulation of matrix metalloproteinase 2 and receptor tyrosine-protein kinase ErbB-2 gene expression in an OSCC rat model were responsible for the clinical outcomes observed (17,18). MTX is a commonly used anticancer agent for various types of cancer, including colon, breast, skin and head and neck cancer (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%